ANALYSIS WEATHER CONDITION SYSTEM DESIGN BASED ON DATABASE BY INTERNET OF THINGS PLATFORM - Musadek, Ahmad; Suryono, Wiwid; Budiarto, Anton; Silk Moonlight, Lady (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
This research focuses on analyzing the design of weather conditions based on a database via the Internet of Things (IoT) platform. The Internet of Things is a rapidly developing technological paradigm, enabling devices to connect to the internet and communicate automatically. In the context of weather monitoring, IoT provides the potential to collect weather data from multiple sources in real-time, providing a deeper understanding of weather and climate change. The aim of this research is to improve the accuracy of weather monitoring and the efficiency of weather monitoring. In order to achieve this goal, this research will design and implement a system using ESP32 and a cloud database system using Firebase which can collect weather data from sensors spread across Surabaya locations. The weather data collected will be stored in a centralized database that can be accessed via the internet. The platform will enable sophisticated data analysis to understand weather changes and long-term weather trends. In addition, this research will make a positive contribution to the understanding of climate change. Weather data collected in large quantities can be used for long-term analysis, helping us understand ongoing climate change trends. This has significant implications in mitigation and adaptation efforts related to climate change. In conclusion, this research has the potential to provide a better understanding of weather and climate change and provide real benefits in various sectors. Through the use of IoT technology, we can maximize weather monitoring and face existing challenges in terms of understanding and handling increasingly dynamic weather changes.